1997
DOI: 10.1246/bcsj.70.1239
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of S2−- and PF2O2-Bridged Dinuclear Ruthenium(IV) Complex Obtained from the Reaction of Disulfide-Bridged Ruthenium(III) Dimer Complex with Dioxygen and Water

Abstract: Reaction of [{Ru(CH3CN)3[P(OMe)3]2}2(μ-S2)](PF6)3 with a mixture of acetylene and O2 gave a novel ruthenium(IV) dimer complex [{Ru(IV)(PFO3)[P(OMe)3]2}2(μ-S)(μ-PF2O2)2]. The newly formed bridging and terminal ligands PF2O2− and PFO32− are produced from the reaction of PF6− with trace amounts of H2O in the solvent. Although acetylene is not incorporated in the final product, it is necessary to accelerate the reaction. Ruthenium(IV) complexes with S2− ligand are rare and only two examples are previously known. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…As the desired cationic species that partner these anions are often rather reactive, any associated anion is also required to be robust to metal‐promoted reactivity. Thus, the anions[PF 6 ] – and [BF 4 ] – , although ubiquitous, are often not the choice for demanding applications due to hydrolysis by adventitious water or fluoride abstraction 2. Although the range of possible anions is large, only a handful are used routinely (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…As the desired cationic species that partner these anions are often rather reactive, any associated anion is also required to be robust to metal‐promoted reactivity. Thus, the anions[PF 6 ] – and [BF 4 ] – , although ubiquitous, are often not the choice for demanding applications due to hydrolysis by adventitious water or fluoride abstraction 2. Although the range of possible anions is large, only a handful are used routinely (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…During our extensive studies on the reactivities of thiolatobridged dinuclear chloro complexes having η 5 -C 5 Me 5 ligands, 5 we have already found that treatment of these complexes with silver cations is effective in producing open coordination sites on the dinuclear centres. 20 Thus, we carried out the reactions of the thiairidaindan complexes with silver cations to generate 21 The presence of the PF 2 O 2 ligand is also suggested by the IR spectrum, which shows ν(PO) bands at 1142 and 1263 cm Ϫ1 , and a ν(PF) band at 841 cm Ϫ1 ; a ν(NC) band due to the isocyanide ligands also appears at 2143 cm Ϫ1 . The molecular structure determined by an X-ray study is depicted in Fig.…”
Section: Reaction Of 2 With Agpfmentioning
confidence: 95%
“…21, 22 The transformation of the PF 6 anion into metal-bound PF 2 O 2 is known to be mediated by transition metals, including iridium and silver. [21][22][23] The oxygen source in these reactions seems to be adventitious water rather than dioxygen. For…”
Section: Reaction Of 2 With Agpfmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution from (iii) was shown to be negligible through spectroscopy studies [41][42][43][44][45][46]. Since our first report of the disulfide-bridged Ru III dinuclear complex, [{Ru(P(OCH 3 ) 3 ) 2 Cl} 2 (l-S 2 )(l-Cl) 2 ] (1) [53], we have developed various C-H cleavage and C-S formation reactions of unsaturated organic molecules on the disulfide ligand [54][55][56][57][58][59][60][61][62][63]. The selenium analogue, [{Ru(P(OCH 3 ) 3 ) 2 Cl} 2 (l-Se 2 )(l-Cl) 2 ] (2), has also been synthesized and similar reactions were performed [64].…”
Section: Reactions Of Dichalcogenide-bridged Dinuclear Ru III Complexesmentioning
confidence: 99%